Pediatric Crohn's disease from onset to adulthood: granulomas are associated with an early need for immunomodulation. (August 2014) - Ideström, Maja; Rubio, Carlos A.; Onelöv, Erik; Henter, Jan-Inge; Fagerberg, Ulrika L.; Finkel, Yigael
Abstract Objective. Childhood onset Crohn's disease (CD) is considered more aggressive than adult onset disease. Epithelioid cell granulomas in intestinal biopsies are one, non-obligate, criterion of CD. We investigated granulomas as markers of CD severity in children followed to adulthood. Material and methods. Forty-five individuals with childhood onset CD were studied from diagnosis until attainment of final height, with data on disease location, medical and surgical management and with detailed growth data analyses. A blinded review of diagnostic biopsies was also performed. Results. We found granulomas in 22/45 (49%) children at diagnosis, altogether in 28/45 (62%) patients during the disease course (median overall follow-up – 12.3 years, range 9.3–18). Granulomas were found in 9/11 (82%) with upper gastrointestinal involvement (cumulatively 17/20, 85%) (p = 0.017 and p = 0.006, respectively). The time from diagnosis to initiating immune modulating treatment (median 4.5 months, range 0–75) was shorter in the granuloma-positive group (16/22) compared to the granuloma-negative group (18/23) (median 33 months, range 2–105; p = 0.01). The median standard deviation score height at diagnosis and final adult height (both adjusted for target height) did not correlate to findings of granulomas. Conclusions. Epithelioid cell granulomas were associated with a shorter time to initiating immune modulating drugs, as a possible sign of more severe disease, but growth was not affected.